Level penalaran aljabar siswa dalam pembelajaran matematika di Sekolah Dasar - Ericha Putri Puspitasari (Jurnal Inovasi Pendidikan Matematika (JIPM), 2019)
This study aims to determine the level of students algebraic reasoning mathematics learning in elementary school. This type of research is qualitative research. The subjects 3 students was fifth grade students of elementary school in Purworejo. The selection of subjects techniques in this study is snowball. Data collection uses learning activities with supporting media in the form of student worksheets, observation sheets, field notes and interviews. Data analysis techniques used from Miles & Hubermen which include three activities namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that there are activities in mathematics learning that have not entered the level of algebraic reasoning put forward by Godino namely level 1,5. These stages are passed gradually from level 0 to level 3 and passed level 1,5, that is, linking the concept of constructing a square with an algebraic symbol before reaching level 2. Subject activity carried out at this level are more about linking objects with other concepts in mathematics learning.